APLIKASI PORTAL MAJALAH CYBER MEDIA BERBASIS ANDROID PORTAL APPLICATION OF CYBER MEDIA MAGAZINE BASE OF ANDROID (Information Technology and Telematics, 2014)
Abstract - The rapid development of the field of news information, make mobile role was very important due to the presence of mobile devices almost all activities can be helped, and the results will be maximized, and faster than having to look at a laptop or computer or manually. In this case Cyber Magazine as one of the media want the addition of technology and media to support the productivity and creativity of the effort that is being built. The use of technology in this case make an application in the form of Android-based mobile to allow users to download in the form of pdf files and read the latest news. Portal Application System was created using XML and HTML programming language and database (SQLite). Portal Application System is also designed using UML system design tools (Unified Modeling Language). In making an application using the RSS method to read the news so that the user can get the latest news on cyber magazine media. It is expected that these applications can help in promoting the magazine editors and users have other means of interaction in the form of a new Cyber Media Magazine. Keywords:  majalah, portal, RSS, android, XML.